2021
DOI: 10.3762/bxiv.2021.10.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synthesis of multiply fluorinated N-acetyl-D-glucosamine and D-galactosamine analogs via the corresponding deoxyfluorinated glucosazide and galactosazide thiodonors

Abstract: Multiple fluorination of glycostructures has emerged as an attractive way of modulating their protein affinity, metabolic stability, and lipophilicity. Here we described the synthesis of a series of mono-, di- and trifluorinated N-acetyl-D-glucosamine and D-galactosamine analogs. The key intermediates were the corresponding multiply fluorinated glucosazide and galactosazide thiodonors prepared from deoxyfluorinated 1,6-anhydro-2-azido-β-D-hexopyranose precursors by ring-opening reaction with phenyltrimethylsil… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…There are no dedicated syntheses of 1,3-difluorinated aminosugars, but it is worth mentioning observations by the Karban group regarding a 1®6 migration process when deoxyfluorinating the 6-position of b-configured thioglycosides (Scheme 128). 429 This process, originally described with a 2-O-benzoylated b-configured methyl galactoside, 145 had been expanded by the Lin group (with bthiophenolates), where they showed that high yields of migration can be achieved, for example in the conversion of 895 to 896 (Scheme 128A). 430 Upon treatment of a mixture of anomers 897 (Scheme 128B, see below Scheme 139 for their synthesis), the Karban group isolated four products, 429 with a-898 arising from clean deoxyfluorination of the a-anomer of 897, whilst b-898, a-899, and b-899 arose from the b-anomer of 897.…”
Section: Fluorination At Positions 1 Andmentioning
confidence: 99%
See 4 more Smart Citations
“…There are no dedicated syntheses of 1,3-difluorinated aminosugars, but it is worth mentioning observations by the Karban group regarding a 1®6 migration process when deoxyfluorinating the 6-position of b-configured thioglycosides (Scheme 128). 429 This process, originally described with a 2-O-benzoylated b-configured methyl galactoside, 145 had been expanded by the Lin group (with bthiophenolates), where they showed that high yields of migration can be achieved, for example in the conversion of 895 to 896 (Scheme 128A). 430 Upon treatment of a mixture of anomers 897 (Scheme 128B, see below Scheme 139 for their synthesis), the Karban group isolated four products, 429 with a-898 arising from clean deoxyfluorination of the a-anomer of 897, whilst b-898, a-899, and b-899 arose from the b-anomer of 897.…”
Section: Fluorination At Positions 1 Andmentioning
confidence: 99%
“…429 This process, originally described with a 2-O-benzoylated b-configured methyl galactoside, 145 had been expanded by the Lin group (with bthiophenolates), where they showed that high yields of migration can be achieved, for example in the conversion of 895 to 896 (Scheme 128A). 430 Upon treatment of a mixture of anomers 897 (Scheme 128B, see below Scheme 139 for their synthesis), the Karban group isolated four products, 429 with a-898 arising from clean deoxyfluorination of the a-anomer of 897, whilst b-898, a-899, and b-899 arose from the b-anomer of 897. The major product was the migration product a-899.…”
Section: Fluorination At Positions 1 Andmentioning
confidence: 99%
See 3 more Smart Citations